A Synoptic Assessment of the Amazon River-Ocean Continuum during Boreal Autumn: From Physics to Plankton Communities and Carbon Flux - Araujo, Moacyr; Noriega, Carlos; Hounsou-gbo, Gbekpo Aubains; Veleda, Doris; Araujo, Julia; Bruto, Leonardo; Feitosa, Fernando; Flores-Montes, Manuel; Lefèvre, Nathalie; Melo, Pedro; Otsuka, Amanda; Travassos, Keyla; et al. (Frontiers in Microbiology, 2017)
The Amazon generates the world’s largest offshore river plume, which covers extensive areas of the tropical Atlantic. The data and samples in this study were obtained during the oceanographic cruise Camadas Finas III in October 2012 along the Amazon River-Ocean Continuum (AROC). The cruise occurred during boreal autumn, when the river plume reaches its maximum eastward extent. In this study, we examine the links between physics, biogeochemistry and plankton community structure along the AROC. Hydrographic results showed very different conditions, ranging from shallow well-mixed coastal waters to offshore areas, where low salinity Amazonian waters mix with open ocean waters. Nutrients, mainly NO3- and SiO2-, were highly depleted in coastal regions, and the magnitude of primary production was greater than that of respiration (negative apparent oxygen utilization). In terms of phytoplankton groups, diatoms dominated the region from the river mouth to the edge of the area affected by the North Brazil Current (NBC) retroflection (with chlorophyll a concentrations ranging from 0.02 to 0.94 mg m-3). The North Equatorial Counter Current (NECC) region, east of retroflection, is fully oligotrophic and the most representative groups are Cyanobacteria and dinoflagellates. Additionally, in this region, blooms of cyanophyte species were associated with diatoms and Mesozooplankton (copepods). A total of 178 zooplankton taxa were observed in this area, with Copepoda being the most diverse and abundant group. Two different zooplankton communities were identified: a low-diversity, high-abundance coastal community and a high-diversity, low-abundance oceanic community offshore. The CO2 fugacity (fCO2sw), calculated from total alkalinity (1450<TA<2394 mol kg-1) and dissolved inorganic carbon (1303<DIC<2062mol kg-1) measurements, confirms that the Amazon River plume is a sink of atmospheric CO2 in areas with salinities <35 psu, whereas, in regions with salinities >35 and higher-intensity winds, the CO2 flux is reversed. Lower fCO2sw values were observed in the NECC area. The ΔfCO2 in this region was less than 5 atm (-0.3 mmol m-2 d-1), while the ΔfCO2 in the coastal region was approximately 50 atm (+3.7 mmol m-2 d-1). During the cruise, heterotrophic and autotrophic processes were observed and are indicative of the influences of terrestrial material and biological activity, respectively.